Management development programs and the readiness for changes: a study in Malaysia - Juhdi, Nurita; Yazit, Farah; Wan Jusoh, Wan Jamaliah; Supar, Norizah (FTMS College Kuala Lumpur, 2015)
The objective of the study is to test the relationship between management development programs and the readiness for changes among young managers in Malaysia. Four development programs were examined namely on-the-job programs, off-the-job programs, assessment and mentoring. The respondents were all below 45 years old and they are either performing professional occupations or in low to middle level positions and must have participated in development programs. 399 employees participated in the study. The Pearson’s correlation test showed that assessment program was not significantly correlated to readiness for changes (r = .035, p > .01). On the other hand, readiness for changes was significantly correlated with the other three MDPs.